2009
DOI: 10.1002/anie.200805273
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Strategy to Drive Nanoparticles into Carbon Nanotubes and the Remarkable Effect of Confinement on Their Catalytic Performance

Abstract: Are you in? Bimetallic PtRu nanoparticles have been selectively confined inside or deposited outside carbon nanotubes (see picture). The confined nanoparticles display significantly higher selectivity and catalytic activity in hydrogenation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
142
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(144 citation statements)
references
References 41 publications
2
142
0
Order By: Relevance
“…A simple and efficient method for the selective confinement of NPs in the inner cavity of CNTs is to use preformed NPs and CNTs functionalized with a long alkyl chain. [5] To graft long-chain alkyl-terminated moieties onto the CNT P surface, CNT P2 was treated with thionyl chloride to produce acetyl chloride, and further treated with hexadecylamine (HDA) to produce the amide surface groups of CNT P3 (Scheme 1). Nitrogen-doped CNTs (CNT N ) were used without further functionalization.…”
Section: Synthesis and Characterization Of The Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple and efficient method for the selective confinement of NPs in the inner cavity of CNTs is to use preformed NPs and CNTs functionalized with a long alkyl chain. [5] To graft long-chain alkyl-terminated moieties onto the CNT P surface, CNT P2 was treated with thionyl chloride to produce acetyl chloride, and further treated with hexadecylamine (HDA) to produce the amide surface groups of CNT P3 (Scheme 1). Nitrogen-doped CNTs (CNT N ) were used without further functionalization.…”
Section: Synthesis and Characterization Of The Supportsmentioning
confidence: 99%
“…[4] Thus, CNTs constitute an interesting alternative to conventional supports due to (i) their high purity that can avoid self-poisoning; (ii) the improved mechanical properties, high electrical conductivity, and thermal stability of these materials; (iii) the high accessibility of the active phase and the absence of any microporosity, which eliminates diffusion and intraparticle mass transfer in the reaction medium; (iv) the possibility of macroscopic shaping of this support; (v) the specific metal-support interactions that can directly affect catalytic activity and selectivity; (vi) the possibility of chemical modification of their surface by doping (for example, with nitrogen) or grafting; and (vii) the possibility of confinement effect in their inner cavity. [5][6][7] Since CNTs are chemically inert, a pretreatment of the surface is needed for metal anchoring that involves oxidation of the CNTs by a strong oxidizing acid, or tedious metal-catalyst synthetic procedures. [8] Commonly, the synthetic methods of metal catalysts involve citrate or borohydride reduction of higher-oxidation-state precursors, and only a few methods produce particles of uniform size.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Molecules and nanomaterials conned inside CNTs have been frequently observed to exhibit modied behaviour and properties with respect to their bulk counterparts. [4][5][6][7] For example, Mao et al predicted via molecular dynamics simulations that CNTs can be used to separate n-butane-methane mixtures because of different diffusion behaviour of these molecules in CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the characteristic shape factor of this material inspires its use as a drug delivery carrier [12] or, more related to catalysis, as a nanoreactor [13]. There are many examples of their use as catalyst support for the immobilisation of either homogeneous catalysts [8,11,14] or metal nanoparticles in the hollow cavity of nanotubes [15][16][17][18]. Previous work in our group showed that, in many cases, hybrid M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%